Characterization of the CrbS/R Two-Component System in Pseudomonas fluorescens Reveals a New Set of Genes under Its Control and a DNA Motif Required for CrbR-Mediated Transcriptional Activation - Sepulveda, Edgardo; Lupas, Andrei N. (Frontiers in Microbiology, 2017)
The CrbS/R system is a two-component signal transduction system that regulates acetate utilization in Vibrio cholerae, P. aeruginosa, and P. entomophila. CrbS is a hybrid histidine kinase that belongs to a recently identified family, in which the signaling domain is fused to an SLC5 solute symporter domain through an, also recently characterized, STAC domain. Upon activation by CrbS, CrbR activates transcription of the acs gene, which encodes an acetyl-CoA synthase (ACS), and the actP gene, which encodes an acetate/solute symporter. In this work, we characterized the CrbS/R system in Pseudomonas fluorescens SBW25. Through the quantitative proteome analysis of different mutants, we were able to identify a new set of genes under its control, which play an important role during growth on acetate. These results led us to the identification of a conserved DNA motif in the putative promoter region of acetate-utilization genes in the Gammaproteobacteria that is essential for the CrbR-mediated transcriptional activation of genes under acetate-utilizing conditions. Finally, we took advantage of the existence of a second SLC5-containing two-component signal transduction system in P. fluorescens, CbrA/B, to demonstrate that the activation of the response regulator by the histidine kinase is not dependent on substrate transport through the SLC5 domain.